Pengaruh Suasana Toko Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Padea Produk Kecantikan SilkyGirl Di Matahari Departement Store Thamrin Medan - Thesalonika Nainggolan; Yahya Tanjung (Journal of Creative Student Research, 2023)
This study aims to determine how influential the store atmosphere variables and service quality are on customer satisfaction in silkygirl beauty products at Matahari Department Store Thamrin Medan. This research method uses quantitative methods with data collection techniques used in this study are interviews and questionnaires. The population used is employees who are consumers of slkyygirl beauty products, with the number of samples taken using the slovin formula, the sample obtained is 94 respondents with α = 0.5 . Data processing using SPSS Version 25 software, with descriptive analysis, multiple regression analysis and hypothesis testing. Based on the results of partial testing, the product has a positive and significant influence on customer satisfaction. Then based on the partial results it can be concluded that H2 is rejected which means that partially service quality does not have a positive and significant effect on customer satisfaction. In testing the F test that has been carried out by the author, it is known that the store atmosphere variable (X1) and service quality (X2) together have a positive and significant effect on customer satisfaction at the Silkygirl store in Matahari Department Store, Medan.